Application of thromboelastography in diagnosing normal pregnancies and pregnancies with complications. Issue 6 (24th April 2022) - Zhao, Hongyan; Cheng, Hui; Huang, Maowen; Mei, Fangchao
Abstract: Background: This observational study aimed to compare the potential application of thromboelastography (TEG) in diagnosing women with normal pregnancy (NP) and women with threatened abortion (TA), missed abortion (MA), embryo arrest (EA), fetal death (FD), history of abnormal pregnancy (HAP), and antiphospholipid antibody syndrome (AA). Methods: According to the relevant clinical criteria, patients were divided into groups, and their blood samples were subjected to TEG. Next, the parameters R, K, α‐angle, MA, LY‐30, G, and coagulation index (CI) were analyzed. Partial correlation analysis was used to analyze correlation between groups of data. LSD‐t test and Dunnett's T3 test were used to analyze continuous variables. Ordinal categorical variables were compared using ordinal logistic regression analysis and estimate odds ratio of risk factors. A receiver operating characteristic (ROC) curve was constructed to detect the ability of TEG to recognize various parameters, and areas under the curve were compared using Delong's test for diagnosing pregnancy‐related diseases. Results: MA had a negative effect on the MA parameter in TEG; EA had a negative effect on the MA and G parameters; HAP had a negative effect on the CI parameter and a positive effect on the R parameter; AA had a negative effect on the CI parameter. Compared with that of the NP group, the G of the EA ( p = 0.014) group and the CI of the TA ( p = 0.036) MA ( p = 0.08) EA ( p = 0.026) HAP ( p = 0.000004) and AA ( p = 0.002) groups were reduced. In the ordinal logistic regression analysis, compared with that of the NP group, the high R value of the HAP group accounted for more than that of the NP group (OR = 48.76, p = 0.001); the high K value of the AA group accounted for more than that of the NP group (OR = 17.00, p = 0.023); the angle value distributions of the TA and AA groups were different from that of the NP group (OR = 3.30, p = 0.039; OR = 0.14, p = 0.029); the low MA value of the MA, EA, and HAP groups accounted for more than that of the NP group (OR = 0.16, p = 0.03; OR = 0.26, p = 0.005; OR = 0.11, p = 0.008); and the low CI value of the HAP group accounted for more than that of the NP group (OR = 0.09, p = 0.005). In the ROC analysis, there were no significant differences in the TEG parameters of pregnant women belonging to the NP and TA, NP and MA, NP and EA, NP and FD, NP and HAP, and NP and AA groups ( p > 0.05). Abstract : We performed thromboelastography on the whole blood of pregnant women, and then analyzed the data. We found that thromboelastography has a good application prospect in the differential diagnosis of normal pregnancy and pregnancy complications.